Overexpression of ZEB2 at the invasion front of colorectal cancer is an independent prognostic marker and regulates tumor invasion in vitro - Kahlert, Christoph; Lahes, Saleh; Radhakrishnan, Praveen; Dutta, Shamik; Mogler, Carolin; Herpel, Esther; Brand, Karsten; Steinert, Gunnar; Schneider, Martin; Mollenhauer, Martin; Reißfelder, Christoph; Klupp, Fee; et al. (Clinical cancer research, 2011)
Purpose: Epithelial-to-mesenchymal transition (EMT) plays a pivotal role in tumor invasion and dissemination. EMT occurs predominantly at the tumor edge where it is induced by cytokines, the extracellular matrix environment, or hypoxia. In the tumor cell, it is further mediated by several transcription factors and microRNAs. The aim of this study was to explore the expression of EMT-associated genes at the invasive front in colorectal cancer and to evaluate their prognostic significance.Experimental Design: We evaluated the expression of 13 EMT-associated genes at the invasion front of 30 colorectal liver metastases by quantitative real-time PCR. Immunostaining against zinc finger E-box-binding homeobox 2 (ZEB2) was carried out on 175 primary colorectal cancer specimens and 30 colorectal liver metastases and correlated to clinical and histopathologic data. DLD-1 cells were transfected with siRNA and subjected to migration and invasion assays.Results: Gene expression analysis and immunohistochemistry showed an upregulation of ZEB2 at the invasion front in primary colorectal cancer and liver metastases. Overexpression of ZEB2 at the invasion front correlated significantly with tumor stage in primary colorectal cancer. Moreover, univariate and multivariate analysis revealed overexpression of ZEB2 at the invasion front as an independent prognostic marker for cancer-specific survival. Downregulation of ZEB2 by siRNA decreased the migration and invasion capacity of DLD-1 cells in vitro.Conclusions: Overexpression of ZEB2 at the invasion front correlates with tumor progression and predicts cancer-specific survival in primary colorectal cancer. Therefore, ZEB2 may be interesting as biomarker and potential target for treatment of colorectal cancer. Clin Cancer Res; 17(24); 7654-63. ©2011 AACR.
Gesehen am 04.07.2022